Knowledge transfer in the context of inter-organizational networks: Foundations and intellectual structures - Danilo Marchiori; Mário Franco (Journal of Innovation & Knowledge (JIK), 2020)
Organizational networks allow the creation and development of knowledge that can be transferred and shared among their components, with an impact on organizations' innovation and performance. Based on this perspective, this study is the result of research on scientific production related to knowledge transfer in the context of inter-organizational networks. Combining various bibliometric techniques, such as co-occurrence analysis, bibliographic coupling and co-citation of documents and authors, 102 articles on the topic published in the main database of scientific knowledge worldwide, Web of Science, were analyzed in detail. The results indicate that knowledge transfer, in the context of organizations, is a recent topic but one that is clearly expanding. Therefore, this subject has increasingly attracted the attention of researchers all over the world. This study also identifies the origins of the current literature on the subject, as well as its foundations and main intellectual structures. The analysis made also presents information that can serve as a basis for future investigators to project, aim for, and attain better results from their research efforts.
Keywords: 650; Knowledge transfer; Inter-organizational networks; Bibliometrics; Co-occurrence; Co-citations; Bibliographic coupling